THE ONGOING IRANIAN SECURITIZATION OF THE UNITED STATES AFTER THE NUCLEAR DEAL: AN ACTOR AND CONTEXT-BASED ANALYSIS - Sevgi Balkan ŞAHİN (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2020)
Abstract: Based on the Copenhagen School’s approach to the securitization theory, this paper examines the Iranian promotion of the United States (US) as a security threat in political, military, economic, and societal sectors despite the nuclear deal concluded in 2015. Analyzing the speeches of the Supreme Leader, Ayatollah Khamenei, as the highest authority in Iran, and the historical context that constitutes the structure of the Iranian-American enmity, the paper shows how Iran has engaged in legitimizing its ongoing securitization discourse vis-à-vis the United States. Within the framework of the socially created discursive historical context in which Iran portrays itself and the US identity, Iran has historically accused the United States for interfering into its domestic affairs for a possible regime change in the country. Emphasizing the embeddedness of such discourses within historical conditions, the paper highlights that Iran exploits the historical context to justify and promote its securitization against the United States. Öz: Bu çalışma, güvenlikleştirme teorisinin Kopenhag Okulu yaklaşımı çerçevesinde, 2015’te imzalanan nükleer anlaşmaya rağmen İran’ın Amerika Birleşik Devletleri’ni (ABD) siyasi, askeri, ekonomik ve toplumsal sektörlerde güvenlik tehdidi olarak tanımlamaya devam etmesini incelemektedir. İran’daki en yüksek siyasi otoriteyi temsil eden Ruhani Lider Ayatollah Hamaney’in konuşmaları ve İran-Amerikan düşmanlığının yapısını oluşturan tarihsel bağlam analiz edilerek İran’ın ABD’ye karşı devam eden güvenlikleştirme söylemini nasıl meşrulaştırmaya çalıştığı gösterilmiştir. Hem kendisinin hem de ABD’nin kimliğini tanımladığı söylemsel tarihsel yapı çerçevesinde İran, ABD’yi tarihsel olarak İran’da rejim değiştirmek amacıyla ülkenin iç işlerine karışmakla suçlamıştır. Bu tür söylemlerin tarihsel koşullardan kaynaklandığını vurgulayan makalede, İran’ın ABD’ye karşı yürüttüğü güvenlikleştirme sürecini meşrulaştırmak için tarihsel bağlamdan yararlandığı ileri sürülmüştür.